Widespread primary, but geographically restricted secondary, human introductions of wall lizards, Podarcis muralis - Sozos N. Michaelides; Geoffrey M. While; Natalia Zajac; Tobias Uller (Molecular Ecology, 2015)
Establishing the introduction pathways of alien species is a fundamental task in invasion biology. The common wall lizard, Podarcis muralis, has been widely introduced outside of its native range in both Europe and North America, primarily through escaped pets or deliberate release of animals from captive or wild populations. Here, we use Bayesian clustering, approximate Bayesian computation ( ABC ) methods and network analyses to reconstruct the origin and colonization history of 23 non‐native populations of wall lizards in England. Our analyses show that established populations in southern England originate from at least nine separate sources of animals from native populations in France and Italy. Secondary introductions from previously established non‐native populations were supported for eleven (47%) populations. In contrast to the primary introductions, secondary introductions were highly restricted geographically and appear to have occurred within a limited time frame rather than being increasingly common. Together, these data suggest that extant wall lizard populations in England are the result of isolated accidental and deliberate releases of imported animals since the 1970s, with only local translocation of animals from established non‐native populations. Given that populations introduced as recently as 25 years ago show evidence of having adapted to cool climate, discouraging further translocations may be important to prevent more extensive establishment on the south coast of England.